2022
DOI: 10.3168/jds.2021-21458
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early herbage cutting and vine leaves on methane emission, urine nitrogen losses, and the milk fatty acid profile of dairy cows

Abstract: Methane mitigation in dairy cows is an essential part of combating global warming. Governments and consumers have become increasingly interested in herbagebased feeding, and premium prices are often paid for these types of dairy products. However, this feeding strategy is presumed to produce more methane per unit of feed or milk than corn silage-or concentrate-based diets due to higher fiber intakes. Immature herbage is preferred to maintain dairy cow performance, but the high content of N and digestible fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…For instance, Emami et al ( 2015 ) observed a linear increase in vaccenic acid, CLA, and punicic acid concentrations in subcutaneous and intramuscular fat with increasing pomegranate seed pulp levels in the diet of kids. More recently, Birkinshaw et al ( 2022 ) reported that tannin-containing feeds, such as vine leaves, lowered the n-6:n-3 fatty acid ratio and increased concentrations of vaccenic and rumenic acids in the milk of dairy cows. On the contrary, according to Baila et al ( 2023 ), phytobiotic additives inhibit ruminal biohydrogenation in the early stages, indicating that lactating ewes fed sainfoin proanthocyanidins had higher milk PUFA contents and a decrease in MUFA intermediates such as vaccenic acid.…”
Section: Effects Of Phytobiotic Additives On Product Qualitymentioning
confidence: 99%
“…For instance, Emami et al ( 2015 ) observed a linear increase in vaccenic acid, CLA, and punicic acid concentrations in subcutaneous and intramuscular fat with increasing pomegranate seed pulp levels in the diet of kids. More recently, Birkinshaw et al ( 2022 ) reported that tannin-containing feeds, such as vine leaves, lowered the n-6:n-3 fatty acid ratio and increased concentrations of vaccenic and rumenic acids in the milk of dairy cows. On the contrary, according to Baila et al ( 2023 ), phytobiotic additives inhibit ruminal biohydrogenation in the early stages, indicating that lactating ewes fed sainfoin proanthocyanidins had higher milk PUFA contents and a decrease in MUFA intermediates such as vaccenic acid.…”
Section: Effects Of Phytobiotic Additives On Product Qualitymentioning
confidence: 99%
“…However, they might prevent ruminants from digesting protein and might lead to digestive issues in animals because they contain tannins. As a result, vine leaves should be added to rations with care and in a balanced manner with other feed sources (Birkinshaw et al, 2022).…”
Section: Introductionmentioning
confidence: 99%